Molecular Diagnostics 12 Tests That Changed Everything - Highsmith, Jr., W. Edward (Molecular and Translational Medicine,, 2014)
Molecular Diagnostics: 12 Tests That Changed Everything focuses on specific laboratory tests and emphasizes how the availability of these tests has altered how clinicians treat their patients.  Presented as a standard outline, each chapter focuses on a specific molecular test  and provides background on the test and its clinical applications. Continuing with some discussion on how the test is done, interpreted, and used clinically, each chapter then concludes with a discussion of how that test has changed the way medicine is practiced with respect to the disease or condition in question. Authored by renowned experts in the field, Molecular Diagnostics: 12 Tests That Changed Everything is a valuable resource for pathologists, pathology residents, laboratory directors, development personnel, lab medicine fellows and those working in the broad area of oncology, infectious disease and genetics.